Bacillus pumilus Cyanide Dihydratase Mutants with Higher Catalytic Activity - Crum, Mary A.; Sewell, B. Trevor; Benedik, Michael J. (Frontiers in Microbiology, 2016)
Cyanide degrading nitrilases are noted for their potential to detoxify industrial wastewater contaminated with cyanide. However, such application would benefit from an improvement to characteristics such as their catalytic activity and stability. Following error-prone PCR for random mutagenesis, several cyanide dihydratases mutants from Bacillus pumilus were isolated based on improved catalysis. Four point mutations, K93R, D172N, A202T and E327K were characterized and their effects on kinetics, thermostability and pH tolerance were studied. K93R and D172N increased the enzyme’s thermostability whereas E327K mutation had a less pronounced effect on stability. The D172N mutation also increased the affinity of the enzyme for its substrate at pH 7.7 but lowered its kcat. However, the A202T mutation, located in the dimerization or the A surface, destabilized the protein and abolished its activity. No significant effect on activity at alkaline pH was observed for any of the purified mutants. These mutations help confirm the model of CynD and are discussed in the context of the protein-protein interfaces leading to the protein quaternary structure.